2013
DOI: 10.2174/15680266113136660214
|View full text |Cite
|
Sign up to set email alerts
|

NAD<sup>+</sup>-Dependent Enzymes at the Endoplasmic Reticulum

Abstract: The post-translational modifications of proteins by mono- and poly-ADP-ribosylation involve the cleavage of βNAD⁺, with the release of its nicotinamide moiety, accompanied by the transfer of a single (mono) or several (poly) ADP-ribose molecules from βNAD⁺ to a specific amino-acid residue of various cellular proteins. Thus, both mono- and poly-ADP-ribosylation are NAD⁺-consuming reactions. ADP-ribosylation reactions have been reported to have important roles in the nucleus, and in mitochondrial activity. Disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The interaction of FasL with the transmembrane protein Fas indeed leads to the activation of caspase 8 and caspase 3, inducing the extrinsic apoptotic pathway [ 28 , 50 ]. Apoptosis is a tightly controlled process, characterized by three pathways, namely, the mitochondrial [ 28 ], endoplasmic reticulum [ 51 ] and death receptor signaling pathways [ 28 ]. Interestingly, Zhang et al have demonstrated, in several cancer cell lines, that the oncoprotein Cysteine-rich intestinal protein 1 (CRIP1) can interact with Fas, enhancing its ubiquitination and degradation and leading to inhibition of caspases 8 and 3, thus underlining the tumor suppressor role of this transmembrane protein [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of FasL with the transmembrane protein Fas indeed leads to the activation of caspase 8 and caspase 3, inducing the extrinsic apoptotic pathway [ 28 , 50 ]. Apoptosis is a tightly controlled process, characterized by three pathways, namely, the mitochondrial [ 28 ], endoplasmic reticulum [ 51 ] and death receptor signaling pathways [ 28 ]. Interestingly, Zhang et al have demonstrated, in several cancer cell lines, that the oncoprotein Cysteine-rich intestinal protein 1 (CRIP1) can interact with Fas, enhancing its ubiquitination and degradation and leading to inhibition of caspases 8 and 3, thus underlining the tumor suppressor role of this transmembrane protein [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 In this regard, the activation of PARP1 by BRCA1 inhibition may decrease the excess autophagy induced by oxidative stress; (iii) endoplasmic reticulum (ER) stress signaling plays an important role in the induction of BRCA1 expression. 21 Mounting evidence has indicated that distinct NAD pools, 22 NAD-dependent PARP1 23 and SIRT1 function 24 all have an important role in the ER; and (iv) it is well known that aberrant proliferation is critical for cancer progression. A substantial body of evidence indicates that loss of function of the tumor suppressor gene BRCA1 plays an important role in promoting cancer cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…ARTD15/PARP16 associates with the endoplasmic reticulum (ER) [146][147][148][149]. It is a single-pass transmembrane protein with the N-terminal region (amino acids 1-280) facing the cytoplasm, and a C-terminal tail facing the ER lumen.…”
Section: Other Marylating Art Enzymes Linked To Cancer and Potential Enzyme Inhibitorsmentioning
confidence: 99%